A review: Percutaneous pulmonary artery stenosis therapy: state-of-the-art and look to the future. (27th December 2018) - Patel, Anuj B.; Ratnayaka, Kanishka; Bergersen, Lisa
Abstract: Stenosis, or narrowing, of the branches of the pulmonary artery is a type of CHD that, if left untreated, may lead to significant complications. Ideally, interventions to treat stenosis occur before significant complications or long-term sequelae take place, often within the first 2 years of life. Treatment depends on specifics of the condition, the presence of other malformations, and age of the child. Research and recent innovation to address these shortcomings have provided physicians with safer and more effective methods of treatment. This has further continued to push the ceiling of pulmonary arterial stenosis treatment available for patients. Despite continuous advancement in angioplasty – such as conventional and cutting balloon – and stenting, each treatment method is not without its unique limitations. New technological developments such as bioresorbable stents can accommodate patient growth and pulmonary artery stenosis treatment. As more than a decade has passed since the review by Bergersen and Lock, this article aims to provide a contemporary summary and investigation into the effectiveness of various therapeutic tools currently available, such as bare metal stents and potential innovations including bioresorbable stents.